Physical activity and associated factors among pregnant women in Ethiopia: facility-based cross-sectional study - Teklehaimanot Tekle Hailemariam; Yosef Sibhatu Gebregiorgis; Berihu Fisseha Gebremeskel; Tsiwaye Gebreyesus Haile; Theresa Monaco Spitznagle (BMC Pregnancy and Childbirth, 2020)
Abstract Background Regular physical activity (PA) has health benefits, including reducing the risk of complications during pregnancy. In Ethiopia, little is known about PA status and its determinants among pregnant women. The purpose of this study was to assess PA status and associated factors among pregnant women attending antenatal care at public and private health facilities in Mekelle, Ethiopia. Methods A facility-based cross-sectional study was conducted. Data was collected from 299 pregnant women using a structured questionnaire. Study participants were selected using a simple random sampling technique. A binary logistic regression was modeled to investigate the statistical significance of independent variables with PA status during pregnancy. Factors associated with PA status were estimated using adjusted odds ratios with 95% confidence intervals and statistical significance was declared at p-value < 0.05. Results 79.3% of the study participants were classified as sedentary. The age group of 26–35 years (AOR: 2.69, 95% CI: 1.07–6.78), attending non-formal education (AOR: 13.50, 95% CI: 2.65–68.91), and women who did not work outside the home (AOR: 5.23, 95% CI: 1.34–20.38) were significantly associated with a higher risk of sedentary activity status. Pregnant women who were married (AOR: 0.26, 95% CI: 0.09–0.73), had two children (AOR: 0.13, 95% CI: 0.03–0.59), traveled an hour or more to health facilities (AOR: 0.31, 95% CI: 0.11–0.89) were protected from being sedentary. Conclusion Sedentary PA status was highly prevalent during pregnancy. Pregnant women in the age group of 26–35 years, with a non-formal education, and women who did not work outside the home had a greater risk of reporting being sedentary. Those who were married, had two children, and traveled an hour or more to health facilities were less likely to be sedentary. Stakeholders (Tigrai regional health bureau, Mekelle University, local NGOs working with pregnant women and societies at large) should give higher emphasis on designing appropriate strategies including educational interventions to overcome barriers to PA during pregnancy.